THE EMPLOYMENT RIGHTS OF DISABLED PEOPLE IN THE REPUBLIC OF MACEDONIA - Postolova, Daniela (Journal of process management and new technologies, 2016)
The analyses of the legal framework concerning the employment rights of the disabled people in the Republic of Macedonia is a significant research challenge because of its importance regarding the employment rights regulation of the disabled people in all. When analyzing the regulation regarding the disabled people, the editing of their rights is of great importance as a source and promoter of many crucial changes and value components when creating a democratic society with no discrimination. Considering this, the influence of the degree of respecting the value principles and standards is particularly emphasized along with the human rights and freedom of the disabled people when it comes to the development of the democracy and the rule of law. The purpose of this paper is to analyze the Macedonian legal framework for the employment rights of the disabled people and to present the provisions of the most important legal acts concerning this subject.